Neutrophil Extracellular Traps Induce MCP-1 at the Culprit Site in ST-Segment Elevation Myocardial Infarction - Hofbauer, Thomas M.; Ondracek, Anna S.; Mangold, Andreas; Scherz, Thomas; Nechvile, Johanna; Seidl, Veronika; Brostjan, Christine; Lang, Irene M. (Frontiers in Cell and Developmental Biology, 2020)
Background Leukocyte-mediated inflammation is crucial in ST-segment elevation myocardial infarction (STEMI). We recently observed that neutrophil extracellular traps (NETs) are increased at the culprit site, promoting activation and differentiation of fibrocytes, cells with mesenchymal and leukocytic properties. Fibrocyte migration is mediated by monocyte chemoattractant protein (MCP)-1 and C-C chemokine receptor type 2 (CCR2). We investigated the interplay between NETs, fibrocyte function, and MCP-1 in STEMI. Methods Culprit site and peripheral blood samples of STEMI patients were drawn during primary percutaneous coronary intervention. MCP-1 and the NETs marker citrullinated histone H3 (citH3) were measured by ELISA while double-stranded DNA was stained with a fluorescent dye. The influence of MCP-1 on NET formation in vitro was assessed using isolated healthy donor neutrophils. Human coronary artery endothelial cells (hCAECs) were stimulated with isolated NETs, and MCP-1 gene expression was measured by ELISA and qPCR. CCR2 expression of culprit site and peripheral blood fibrocytes was characterized by flow cytometry. Healthy donor fibrocyte receptor expression and chemotaxis were investigated in response to stimulation with MCP-1 and NETs in vitro. Results NETs and concentrations of MCP-1 were increased at the culprit site of 50 consecutive STEMI patients. NET stimulation of hCAECs induced transcription of ICAM-1, IL-6 and MCP-1, and secretion of MCP-1. MCP-1 promoted NET formation of healthy donor neutrophils in vitro. An increasing MCP-1 gradient correlated with fibrocyte accumulation at the culprit site. Locally increased MCP-1 levels were negatively correlated with CCR2 expression on fibrocytes. MCP-1 and NETs induced CCR2 downregulation on fibrocytes in vitro. NETs did not function as a chemotactic stimulus for fibrocytes or monocytes and could block migration in response to MCP-1 for both cell populations. Conclusion NETs function as signaling scaffolds at the culprit site of STEMI. NETs assist MCP-1 and ICAM-1 release from culprit site coronary artery endothelial cells. MCP-1 facilitates further NETosis. Monocytes enter the culprit site along an MCP-1 gradient, to transdifferentiate into fibrocytes in the presence of NETs.